First eigenvalue of submanifolds in Euclidean space - Kairen Cai (International Journal of Mathematics and Mathematical Sciences)
We give some estimates of the first eigenvalue of the Laplacian for compact and non-compact submanifold immersed in the Euclidean space by using the square length of the second fundamental form of the submanifold merely. Then some spherical theorems and a nonimmersibility theorem of Chern and Kuiper type can be obtained.